Konsep Kafa’ah: Studi Komparasi Hukum Islam Pasal 61 dan Kitab Al- Fiqh Al Manhaji ‘Ala Madzhab Al Imam Al-Syafi’i - Siti Munawaroh (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
One of the problems to find a good partner is the problem of kafa'ah. When associated with marriage, kafa'ah is defined as a balance between a prospective husband and wife, in terms of position (hasab), religion (dn), descent (nasab), and the like. Actually, Kafa'ah is not a condition for the validity of a marriage, in the sense that the marriage contract is still valid even though the bride and groom are not together if they are pleased. The author here will examine the concept of Islamic Law Article 61 and the Book of Al-Fiqh Al Manhaji 'Ala Madzhab Al Imam Al-Shafi'i. This research is a literature research with a qualitative approach which is then analyzed by descriptive-analytic-comparative. As for the results of this study, there are differences in the concept of kafa'ah in KHI chapter 61 and the book of Fiqh Al Manhaji. In KHI sekufu in marriage is seen only in terms of religion while in the book of Fiqh Al Manhaji, sekufu in marriage can be seen from three things (aspects) namely religion and goodness, livelihood and safety from defects. Thus, it is important for someone who is getting married to measure the standards of himself and his potential partner, so that the household runs in harmony. The importance of this research is because the Compilation of Islamic Law is one of the references used by the Religious Courts in Indonesia. While the book Al-Fiqhu Al-Manhaji 'Ala Madzhab Al-Imam Al-Syafi'i is one of the books of fiqh that is well-known among the Imam Shafi'i schools in Indonesia.